Enantiospecific recognition of 2-butanol by an inherently chiral cavitand in the solid state. Issue 24 (8th June 2017) - Brancatelli, G.; Nicosia, C.; Barboza, T.; Guy, L.; Dutasta, J.-P.; De Zorzi, R.; Demitri, N.; Dalcanale, E.; Geremia, S.; Pinalli, R.
Abstract : An inherently chiral cavitand is reported, featuring a disymmetric cavity capable of enantiospecific recognition of 2-butanol. Abstract : A new inherently chiral cavitand is described, in which the desymmetrization of the rigid concave cavity is achieved by introducing three different bridging groups at the upper rim, namely two inward PO groups, one inward PS moiety and one methylene bridge in the AABC mode. The racemic mixture of cR and cS enantiomers is resolved by semi-preparative chiral HPLC and the enantiopurity confirmed through circular dichroism. The properties of the enantiopurecR-cav in the enantioselective recognition of racemic 2-butanol is studied by co-crystallization experiments. The exclusive formation of the complex R -BuOH@cR-cav demonstrates thatcR-cav is able to discriminate between the two enantiomers of the alcohol in the solid state. The enantiospecific recognition exhibited by the c R-cav towards racemic 2-butanol is particularly relevant because of the low degree of chirality of the alcohol (1.9 calculated by CCM algorithm).